Analisis Tafsir Maqāṣidī Muḥammad Ṭāḥir bin ‘Āsyūr Pada Ayat Qiṣāṣ - Rohman, Abdul; Zulaiha, Eni; Taufiq, Wildan (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
AbstractThis paper discusses the concept of maqāṣidī Ibn 'Asyūr's interpretation and its implementation in qiṣāṣ verses. The purpose of this paper is to find out the construction of maqāṣidī Ibn 'Āsyūr's interpretation and the implementation of the interpretation of the qiṣāṣ verses in the Qur'an. The method used is descriptive analysis with literature study. The analytical approach used is the Jasser Audah systems approach. The result obtained is that the maqāṣidī interpretation constructed by Ibn 'Āsyūr is generally oriented towards achieving benefit and rejecting damage. Its achievement is based on the realization of safeguarding the five most basic things, namely protecting religion, soul, lineage, property, and mind; This benefit is realized in three forms of maqāṣid, namely maqāṣid 'ām (general), maqāṣid khāṣṣ (special) and maqāṣid juziyyah (partially); Implementation of the interpretation of the maqāṣidī Ibn 'Āsyūr concept in the verse qiṣāṣ results in an interpretation that qiṣāṣ law has five main objectives (maqāṣid), namely enforcing fair laws, preventive goals, nuanced equality, protecting life and creating stability and security of society.Keywords: Ibn ‘Āsyūr; Interpretation of Maqāṣidī; Qiṣāṣ. AbstrakTulisan ini membahas tentang konsep tafsir maqāṣidī Ibn 'Asyūr dan implementasinya pada ayat-ayat qiṣāṣ. Tujuan dari tulisan ini adalah untuk mengetahui konstruksi tafsir maqāṣidī Ibn 'Āsyūr dan implementasi penafsiran pada ayat-ayat qiṣāṣ dalam Al-Qur’an. Metode yang digunakan adalah deskriptif-analisis dengan studi pustaka. Pendekatan analisis yang digunakan adalah pendekatan sistem Jasser Audah. Hasil yang didapatkan adalah bahwa tafsir maqāṣidī yang dikonstruksikan oleh Ibn 'Āsyūr pada umumnya berorientasi pada pencapaian kemaslahatan dan penolakan pada kerusakan. Pencapaiannya didasarkan pada terjaganya lima hal yang paling mendasar, yaitu menjaga agama, jiwa, keturunan, harta dan akal; kemaslahatan ini diwujudkan dalam tiga bentuk maqāṣid, yaitu maqāṣid 'ām (umum), maqāṣid khāṣṣ (khusus) dan maqāṣid juziyyah (sebagian); Implementasi penafsiran konsep maqāṣidī Ibn 'Āsyūr dalam ayat qiṣāṣ menghasilkan tafsir bahwa hukum qiṣāṣ memiliki lima tujuan utama (maqāṣid), yaitu menegakkan hukum yang berkedilan, tujuan preventif, bernuansa persamaan hukum, melindungi kehidupan serta menciptakan stabilitas dan keamanan masyarakat. Kata Kunci: Ibn ‘Āsyūr; Qiṣāṣ; Tafsir Maqāṣidī.